Performance Management and Budgeting : How Governments Can Learn from Experience. - Redburn, F. Stevens (Taylor and Francis, 2015)
This book provides a fresh look at the process by which governments hold themselves accountable to their citizens for performance. Unlike the plethora of other books in the field, it examines all aspects of the Performance Management and Budgeting issue, not only from the federal, state, and local perspectives, but also internationally in both developing and developed countries. Covering both conceptual and theoretical frameworks in performance management and budget, the book analyzes the effectiveness of different approaches. Featuring insights from a group of distinguished contributors, it ti.